The Impact of Small-for-gestational-age on Neonatal Outcome Among Very-low-birth-weight Infants - Li-Yi Tsai; Yi-Ling Chen; Kuo-Inn Tsou; Shu-Chi Mu (Pediatrics and Neonatology, 2015)
This study aimed to evaluate the impact of small-for-gestational-age (SGA) on mortality and morbidity in very-low-birth-weight (VLBW) infants. Methods: We conducted a retrospective cohort study on VLBW infants registered at the Premature Baby Foundation of Taiwan between 2007 and 2011. All 21 neonatal departments in Taiwan participated in the data collection, and a total of 4636 VLBW infants were registered during the study period. The SGA group (n = 560) was selected from the database on the basis of birth weight below the 10th percentile for gestational age, whereas the appropriate-weight-for-gestational-age (AGA) group (n = 1120) included infants randomly selected via incidence density sampling with a 2:1 match for each SGA case. The association of SGA with individual outcome variables including mortality, respiratory distress syndrome, necrotizing enterocolitis, retinopathy of prematurity (ROP), intraventricular hemorrhage, periventricular leukomalacia, and bronchopulmonary dysplasia (BPD) was evaluated after adjustment for potential confounders. Results: The SGA group was associated with increased risks of mortality [odds ratio (OR) 1.89; 95% confidence interval (CI) 1.39‒2.58], severe ROP (OR 1.56; 95% CI 1.13–2.14), and BPD (OR 2.08; 95% CI 1.58–2.75) compared to the AGA group. Further subgroup analysis showed that SGA had significant effects on mortality in the VLBW infants with a gestational age of 24–29 weeks, as well as on BPD in those with a gestational age of 27–32 weeks. By contrast, the association of SGA with severe ROP was only significant in the VLBW infants with a gestational age of 27–29 weeks. Conclusion: Our data provide evidence that SGA may be associated with increased risks of neonatal mortality, ROP, and BPD in VLBW infants.